PEMBINAAN PERPUSTAKAAN DESA MELALUI PENGOLAHAN PERPUSTAKAAN DI PERPUSTAKAAN NAGARI SUMANIK - Ardana Maghfirah; Sri Wahyuni (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2023)
In organizing collection materials in the library, it cannot be separated from the application of a classification system, which is used as a class determination in the alignment of collections on shelves. Classification activities are very useful for libraries, because they have an impact on users when looking for information. In addition, choosing the right classification system also makes it easier for librarians to organize library materials. Therefore, this research was conducted to analyze the classification system at the Nagari Sumaniak Library. The purpose of this research is to find out the application of the classification system, as well as the procedures for carrying out classification activities in the library. The research method used is descriptive method with a qualitative approach. The data collection technique in this study was to analyze the data and the results of observations. The results of this study include research on the management of library materials, and procedures for classifying library collections. Keywords: Classification system, Library Materials, Nagari Sumaniak Library